Sistem Pendukung Keputusan Penentuan Instruktur Bahasa Inggris Dengan Metode Simple Additive Weighting (SAW) - Hery Sunandar; Denni M Rajagukguk (Yayasan Kita Menulis, 2019)
Use of Decision Support Systems (SPK) can help someone in making decisions that are accurate and right on target. Many problems can be solved by using SPK. This study aims to design SPK with SAW Method for the determination of English instructors. This system utilizes criteria and weights. There are 6 main criteria for gauges. Based on the SPK analysis using the SAW method the results of performance effectiveness are obtained. Based on the SAW method the effectiveness of the determination of the English instructor is influenced by many factors that are the criteria of the decision support system.